Aid to agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Aid to agriculture: reversing the decline by Joachim von Braun F Hopkins Detlev Puetz and Rajul Pandya-Lorch International Food Policy Research Institute 1200 Seventeenth Street N W Washington DC 20036-3006 USA